Experimental Assessment of 10 Gbps 5G Multicarrier Waveforms for High-Layer Split U-DWDM-PON-Based Fronthaul - Sarmiento, Samael; Altabas, Jose A.; Spadaro, Salvatore; Lazaro, Jose A. (Journal of lightwave technology, 2019)
The current constant growth in mobile networks' traffic demands caused by the popularization of cloud and streaming services on personal devices, requires architectural changes so as to fulfill all new 5G mobile network requirements. Cloud access radio network (C-RAN) architecture in combination with the massive deployment of small cell antenna sites have recently been proposed as a promising solution but will be demanding for high-capacity mobile fronthaul links. An efficient way for performing that connectivity is to make use of the dense wavelength multiplexing passive optical network (DWDM-PON) infrastructure. In this context, orthogonal frequency division multiplexing (OFDM) has been extensively explored as a potential candidate. Nevertheless, the main drawback of OFDM is its high out-of-band radiation. In order to overcome that drawback, new 5G multicarrier waveforms (FBMC, UFMC, and GFDM) have recently been proposed. In this paper, we experimentally assess and compare 10 Gbps 32-QAM-OFDM/FBMC/UFMC/GFDM system performance for high-layer split ultra-DWDM-PON-based fronthaul using a radio-over-fiber technique. The performance has been done in terms of spectral efficiency, peak-to-average power ratio, spectral density, and receiver sensitivity. In particular, intensity-modulation with direct-detection and quasi-coherent-detection have been considered. In order to improve the multicarrier system energy efficiency, the effect of using a hard clipping technique over transmitted signals is also studied. Finally, we evaluated the crosstalk interference between two adjacent channels of the same modulation scheme, as a function of their electrical frequency span for downlink application.